Does suprahyoid muscle complex pull cause relapse following genial advancement by distraction osteogenesis? An electromyographic study. Issue 7 (September 2022) - Lal, Babu; Alagarsamy, Ragavi; Bhutia, Ongkila; Roychoudhury, Ajoy; Yadav, Rahul; Muthukrishnan, Suriya Prakash
Abstract: Active pull of the suprahyoid muscle complex (SMC) was thought to be the main contributor of relapse in mandibular or chin advancement, but literature evidence lacks human studies that assess the role of the SMC following genial advancement (GeA). This study therefore aimed to analyse the influence of SMC pull on relapse following GeA by distraction osteogenesis based on electromyographic (EMG) changes. EMG was recorded and analysed preoperatively (T0), at four months (T1), and at one-year follow up (T2) at three submental regions during two different activities. The outcome variables were EMG changes of the SMC, and hard and soft tissue relapse. Assessment was carried out by comparison of EMG and lateral cephalograms taken at T0, T1, and T2. Ten patients (7 male and 3 female; median (SD) age 21.2 (3.99) years, range 18-28) were included. The EMG values revealed a statistically significant reduction between T0 and T1. T2 values were not higher than T0 during any activity. The results of Pearson's correlation demonstrated no significant relation between the amount of relapse and change in EMG values. This study concluded that active pull of the SMC is not the actual reason for skeletal relapse in chin or mandibular advancement. Passive biomechanics such as adnexial or muscular connective tissue, and paramandibular periosteum pull with native bone remodelling might be the prime reasons for relapse. However, further large sample studies are warranted to find the actual causes of relapse.